2003
DOI: 10.3758/bf03196535
|View full text |Cite
|
Sign up to set email alerts
|

Strategic influences on recollection in the exclusion task: Electrophysiological evidence

Abstract: One assumption underlying the use of the exclusion task as part of the process dissociation procedure is that studied items are successfully excluded only when they are recollected. The present study employed event-related potentials (ERPs) to demonstrate that successful exclusion does not necessarily require recollection. In two experiments, the study tasks for to-be-excluded items were identical, but the tasks employed with target items differed, giving better memory for these items in Experiment 1 than in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 34 publications
12
94
3
Order By: Relevance
“…Turning to the parietal positivity, the absence of recollection eVects in the ERPs to excluded, although in some sense recognised, items supports the observation of Herron and Rugg (2003b) that recollection is not a necessary condition for an exclusion decision. Instead, the data suggest that negative decisions can be based on a subset of the available evidence.…”
Section: Old-new Evectsmentioning
confidence: 76%
See 2 more Smart Citations
“…Turning to the parietal positivity, the absence of recollection eVects in the ERPs to excluded, although in some sense recognised, items supports the observation of Herron and Rugg (2003b) that recollection is not a necessary condition for an exclusion decision. Instead, the data suggest that negative decisions can be based on a subset of the available evidence.…”
Section: Old-new Evectsmentioning
confidence: 76%
“…Do to-be-excluded stimuli produce involuntary old-new eVect in ERPs (cf. Herron & Rugg, 2003a, 2003b? Some memory eVects -such as recollection -are typically voluntary, whereas others -such as priming -appear to be beyond conscious control.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, retrieval processing may operate within the context of support processes that can themselves influence whether recollection succeeds (Rugg & Wilding, 2000). For example, electrophysiological evidence has shown that the adoption of an appropriate retrieval orientation is predictive of recollection success (Herron & Rugg, 2003). One important implication of this view is that even when recollection fails, the memory being sought may nonetheless be retrievable using different cues, or by an alternative process such as familiarity.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropsychology literature has corroborated these assumptions and suggests that automatic retrieval from long-term memory is limited to the recognition of single items (or highly unitized chunks). By contrast, associative retrieval of arbitrary bindings, such as object-location, word-temporal position, or face-name pairings, rests on slower retrieval processes that have been shown to be strategically controlled (Ecker, Zimmer, & Groh-Bordin, 2007;Herron & Rugg, 2003;Mecklinger, 2000;Meiser, Sattler, & Weißer, 2008). For instance, Ecker et al (2007) have shown that only intrinsic item features (such as an object's color or font) but not context features (such as background or location information) automatically affect object recognition, whereas contextual information is selectively retrieved via controlled recollection if relevant for the task.…”
Section: Instantaneous Retrieval?mentioning
confidence: 99%